Thiophene-Linked 1,2,4-Triazoles: Synthesis, Structural Insights and Antimicrobial and Chemotherapeutic Profiles - Nada A. El-Emam; Mahmoud B. El-Ashmawy; Ahmed A. B. Mohamed; El-Sayed E. Habib; Subbiah Thamotharan; Mohammed S. M. Abdelbaky; Santiago Garcia-Granda; Mohamed A. A. Moustafa (MDPI AG, 2024)
The reaction of thiophene-2-carbohydrazide 1 or 5-bromothiophene-2-carbohydrazide 2 with various haloaryl isothiocyanates and subsequent cyclization by heating in aqueous sodium hydroxide yielded the corresponding 4-haloaryl-5-(thiophen-2-yl or 5-bromothiophen-2-yl)-2,4-dihydro-3H-1,2,4-triazole-3-thione 5a-e. The triazole derivatives 5a and 5b were reacted with different secondary amines and formaldehyde solution to yield the corresponding 2-aminomethyl-4-haloaryl-2,4-dihydro-3H-1,2,4-triazole-3-thiones 6a-e, 7a-e, 8, 9, 10a and 10b in good yields. The in vitro antimicrobial activity of compounds 5a-e, 6a-e, 7a-d, 8, 9, 10a and 10b was evaluated against a panel of standard pathogenic bacterial and fungal strains. Compounds 5a, 5b, 5e, 5f, 6a-e, 7a-d, 8, 9, 10a and 10b showed marked activity, particularly against the tested Gram-positive bacteria and the Gram-negative bacteria Escherichia coli, and all the tested compounds were almost inactive against all the tested fungal strains. In addition, compounds 5e, 6a-e, 7a-d and 10a exhibited potent anti-proliferative activity, particularly against HepG-2 and MCF-7 cancer cell lines (IC50 < 25 μM). A detailed structural insight study based on the single crystals of compounds 5a, 5b, 6a, 6d and 10a is also reported. Molecular docking studies of the highly active antibacterial compounds 5e, 6b, 6d, 7a and 7d showed a high affinity for DNA gyrase. Meanwhile, the potent anti-proliferative activity of compounds 6d, 6e and 7d may be attributed to their high affinity for cyclin-dependent kinase 2 (CDK2).